Antihypertensive polytherapy in Australia: prevalence of inappropriate combinations, 2013–2018. Issue 8 (August 2020) - Falster, Michael O.; Buckley, Nicholas A.; Brieger, David; Pearson, Sallie-Anne
Abstract : Objectives: To estimate the prevalence of inappropriate antihypertensive polytherapy in Australia. Methods: We used a nationally representative 10% sample of Pharmaceutical Benefits Scheme (PBS) eligible Australians and their dispensing history to identify people aged 18+ years exposed to at least one PBS-listed antihypertensive between 2012 and 2018. We measured prevalence of antihypertensive polypharmacy (≥40 days concomitant exposure), inappropriate antihypertensive combinations (against guideline recommendations; within-class polytherapy) and combinations to be used with caution. Results: Almost half (47.5%) of people using antihypertensives in 2018 experienced polytherapy. Among these, 2.4% had an inappropriate combination (1.5% against guidelines; 1.0% within-class polytherapy). Inappropriate combinations were more prevalent in people experiencing polytherapy with three (3.7%) or four (16.1%) antihypertensive medicines than people on dual therapy (0.7%). Inappropriate combinations occurred at a lower rate in people using fixed-dose rather than free-drug combinations for dual therapy (0 vs. 0.7%) and in those using three antihypertensives (2.4 vs. 7.3%); this was not the case for people using four or more antihypertensives (15.5 vs. 16.1%). Between 2013 and 2018, the prevalence of antihypertensive polytherapy was relatively stable (49–47%); however, the prevalence of inappropriate combinations among these patients halved (from 5.1 to 2.4%). Conclusion: Antihypertensive polytherapy in Australia is common, but the prevalence of inappropriate combinations is low and decreasing over time, suggesting strong awareness of Australian clinical guidelines. However, in 2018, approximately 49 000 Australian adults experienced inappropriate polytherapy; prescribing of fixed-dose combinations in patients on dual or triple therapy may further reduce this inappropriate care, although increased vigilance treating patients with more than 3 antihypertensives is required. Abstract : Supplemental Digital Content is available in the text